THE EFFECT OF SUPERITEM LEARNING MODEL ON INCREASING STUDENTs LEARNING ACHIEVEMENTS - Muhammad Kholidin Maftuh; Dayat Hidayat ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study aims to see the influence of super-learning models on student achievement. This research is rarely done because of the lack of literature. In learning mathematics, it should not be direct to complex or complex concepts, but it must start from a simple concept. The aim to be achieved in this study is to determine whether or not the influence of super-learning learning models on quadrilateral learning on improving student learning achievement. The population in this study were Pangkalan 2 junior high school students. Samples were taken using makeshift sample techniques where the entire population was sampled; one class was made into the experimental class namely class VII A; and one class was made into the control class namely class VII B. The method in this study was experimental method. There contained research on students of SMPN 2 Pangkalan Karawang regency class VII with quadrilateral. The instruments in this study were Student Worksheets and achievement tests given at the initial test and final test. Based on the results of the analysis and testing of hypotheses, it was concluded that the use of Superitem learning models had a positive effect on improving student learning achievement, and there were differences in the increase in learning achievement between students who had mathematical learning using super-learning models with students who used mathematics learning conventional learning.